Imbalance of proresolving lipid mediators in persistent allodynia dissociated from signs of clinical arthritis. Issue 9 (September 2020) - Allen, Benjamin L.; Montague-Cardoso, Karli; Simeoli, Raffaele; Colas, Romain A.; Oggero, Silvia; Vilar, Bruno; McNaughton, Peter A.; Dalli, Jesmond; Perretti, Mauro; Sher, Emanuele; Malcangio, Marzia
Abstract : Abstract: Rheumatoid arthritis-associated pain is poorly managed, often persisting when joint inflammation is pharmacologically controlled. Comparably, in the mouse K/BxN serum-transfer model of inflammatory arthritis, hind paw nociceptive hypersensitivity occurs with ankle joint swelling (5 days after immunisation) persisting after swelling has resolved (25 days after immunisation). In this study, lipid mediator (LM) profiling of lumbar dorsal root ganglia (DRG), the site of sensory neuron cell bodies innervating the ankle joints, 5 days and 25 days after serum transfer demonstrated a shift in specialised proresolving LM profiles. Persistent nociception without joint swelling was associated with low concentrations of the specialised proresolving LM Maresin 1 (MaR1) and high macrophage numbers in DRG. MaR1 application to cultured DRG neurons inhibited both capsaicin-induced increase of intracellular calcium ions and release of calcitonin gene-related peptide in a dose-dependent manner. Furthermore, in peritoneal macrophages challenged with lipopolysaccharide, MaR1 reduced proinflammatory cytokine expression. Systemic MaR1 administration caused sustained reversal of nociceptive hypersensitivity and reduced inflammatory macrophage numbers in DRG. Unlike gabapentin, which was used as positive control, systemic MaR1 did not display acute antihyperalgesic action. Therefore, these data suggest that MaR1 effects observed after K/BxN serum transfer relate to modulation of macrophage recruitment, more likely than to direct actions on sensory neurons. Our study highlights that, in DRG, aberrant proresolution mechanisms play a key role in arthritis joint pain dissociated from joint swelling, opening novel approaches for rheumatoid arthritis pain treatment. Abstract : Supplemental Digital Content is Available in the Text.In inflammatory arthritis, we show an imbalance of proresolving bioactive lipid mediators in dorsal root ganglia, under persistent nociceptive states, and antinociceptive effects of maresin-1 administration.